Chapter Fazioni e popolo in una provincia del dominio pontificio fra XIII e XIV secolo - MINEO, Ennio (Reti Medievali E-Book, 2021)
Between the 13th and 14th centuries, a number of cities in the inchoative papal state experimented a system of self-government that allowed the Guelph and Ghibelline factions, formally represented in those same bodies on an equal footing, to work alongside the more strictly communal magistracies. The case of Todi is rather well known, given the role that Bartolo da Sassoferrato assigns to it in his Tractatus de guelphis et gebellinis (ca. 1350), but current research has already ascertained that this political tradition appeared at least around 1260. Some evidence can suggest, however, that some form of integration of factions into the local institutional framework was possible elsewhere, and not far away, at Amelia for example. Here, in the new statute of the people (1343), we find a distribution of the roles of the priorato based on factions. At Todi, in 1337, something similar had happened: the statute issued that year followed the establishment of an explicitly popular regime which, in continuity with local tradition, integrated Guelphs and Ghibellines within it. The examples of these, and perhaps other, communities in the province of the Patrimonio di San Pietro in Tuscia can thus add some useful elements to the discussion of the problem of factions and their role in the communal and post-communal political order, and in particular the relationship between the people (popolo) as an institutional system and the parties.